An automated micromethod for measuring iron concentration in serum using thioglycollic acid and bathophenantroline sulphonate - Brozović, B. (1974)
An automated micromethod for measuring iron concentration in serum employing thioglycollic acid and bathophenantroline sulphonate as reducing agent and chromogen respectively, is described. Measurements are carried out using an AutoAnalyzer (Technicon) and require 0·1 ml of sample. The reproducibility, assessed by the mean coefficient of variation (1·9%), and the mean recovery of iron added to samples (99·5%), as well as the correlation between the serum iron values estimated by the described method and the method recommended by the Expert Panel on Iron of the International Committee for Standardization in Haematology (r = 0·9779; p < 0·001; y = 0·9713 x −0·0546), is highly satisfactory. The method can also be used for measuring total ironbinding capacity of serum. The method appears equally suitable for routine work and research studies when a large number of samples and a small volume of serum are available.